Limited referral to nephrologists from a tertiary geriatric outpatient clinic despite a high prevalence of chronic kidney disease and anaemia - Boudville Neil; Muthucumarana Kalindu; Inderjeeth Charles (BMC Geriatrics, 2012)
Abstract Background Chronic kidney disease (CKD) is increasing in prevalence world-wide with the largest growth being in the elderly. The aim of this study was to examine the prevalence of CKD in a geriatric outpatient clinic within a tertiary hospital and its association with anaemia and mortality with a focus on the referral patterns towards nephrologists. Methods Retrospective study utilising administrative databases. The cohort was defined as all patients that attended the geriatric outpatient clinics of a single tertiary hospital within the first 3 months of 2006. Patients were followed for 18 months for mortality and referral to a nephrologist. Results The mean Glomerular filtration rate (eGFR) of the 439 patients was 67.4 ± 29.1 mL/min/1.73 m2 (44% <60 mL/min/1.73 m2). 11.8% had a haemoglobin < 110 g/L, with anaemia being significantly associated with kidney function in those with a eGFR < 60 mL/min/1.73 m2 (p = 0.0092). Kidney function and anaemia were significantly associated with mortality on multivariate analysis (p = 0.019 and p = 0.0074). After 18 months, 8.8% of patients with CKD were referred to a nephrologist. Conclusion Despite a high prevalence of CKD in patients attending a geriatric outpatient clinic and its association with anaemia and mortality, few of these patients were referred to a nephrologist. An examination of the reasons behind this bias is required.